The Lateral Preoptic Area and Its Projection to the VTA Regulate VTA Activity and Drive Complex Reward Behaviors - Gordon-Fennell, Adam; Gordon-Fennell, Lydia; Desaivre, Stève; Marinelli, Michela (Frontiers in Systems Neuroscience, 2020)
The ventral tegmental area (VTA) underlies motivation and reinforcement of natural rewards. The lateral preoptic area (LPO) is an anterior hypothalamic brain region that sends direct projections to the VTA and to other brain structures known to regulate VTA activity. Here, we investigated the functional connection between the LPO and subpopulations of VTA neurons and explored the reinforcing and valence qualities of the LPO in rats. We found that the LPO and the LPO→VTA pathway inhibits VTA GABA neurons and has mixed effects on VTA dopamine neurons. Furthermore, we found that the LPO supports operant responding but drives avoidance, and we explored the apparent discrepancy between these two results. Finally, using fiber photometry, we show that the LPO signals aversive events but not rewarding events. Together, our findings demonstrate that the LPO modulates the activity of the VTA and drives motivated behavior and represents an overlooked modulator of reinforcement.